Evaluating change in body image concerns following a single session digital intervention. (March 2023) - Nemesure, Matthew D.; Park, Chloe; Morris, Robert R.; Chan, William W.; Fitzsimmons-Craft, Ellen E.; Rackoff, Gavin N.; Fowler, Lauren A.; Taylor, C. Barr; Jacobson, Nicholas C.
Abstract: Many young individuals at risk for eating disorders spend time on social media and frequently search for information related to their body image concerns. In a large randomized study, we demonstrated that a guided chat-based intervention could reduce weight and shape concerns and eating disorder pathology. The goal of the current study was to determine if a modified single session mini-course, derived from the aforementioned chat-based intervention, could reduce body image concerns among individuals using eating disorder related search terms on a social media platform. Over a two-month period of prompting individuals, 525 people followed the link to the web-based application where the intervention was hosted and subsequently completed the mini-course. This resulted in a significant improvement on the one-time body image satisfaction question pre-to post intervention ( p  < .001) with a moderate effect size (Cohen's d = 0.54). A d ditionally, individuals completing the program showed significant improvement on motivation to change their body image ( p  < .001) with a small effect size (Cohen's d = 0.28). Additionally, users reported that the program was enjoyable and easy to use. These results suggest that a single session micro-intervention, offered to individuals on social media, can help improve body image. Highlights: Digital interventions are impactful when adapted and delivered in an online setting. The mini-course improved body image for those searching ED terms on social media. The mini-course was well received and can be delivered at scale.